2019
DOI: 10.5194/os-15-307-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bottom sediment resuspension events observed in a micro-tidal bay

Abstract: Abstract. In this study we investigate the variability in near-bottom turbidity in Alfacs Bay (in the northwestern Mediterranean Sea). The bay is characterized by a micro-tidal environment and seiching activity that may lead to flow velocities of more than 50 cm s−1. A set of current meters and optical sensors were mounted near the sea bottom to acquire synchronous hydrodynamic and optical information from the water column. The time-series observations showed an evident relation between seiche activity and sed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Recently, Díez-Minguito and de Swart [37] demonstrated that as suspended sediment concentration increased, so did Chl a concentrations at spring and neap tidal scales due to simultaneous resuspension of sediment and Chl a containing biomass induced by tidal shear stress. In this sense, Grifoll et al [41] showed evident relations in time-series observations in Alfacs Bay between strong wind events and an increase in near-bottom turbidity. Turbidity measurements in Fangar Bay (Figure 2g) have shown a relationship between the increase in near-bottom turbidity and intense wind episodes making plausible the incorporation of Chl a containing biomass in the water column during the wind episodes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, Díez-Minguito and de Swart [37] demonstrated that as suspended sediment concentration increased, so did Chl a concentrations at spring and neap tidal scales due to simultaneous resuspension of sediment and Chl a containing biomass induced by tidal shear stress. In this sense, Grifoll et al [41] showed evident relations in time-series observations in Alfacs Bay between strong wind events and an increase in near-bottom turbidity. Turbidity measurements in Fangar Bay (Figure 2g) have shown a relationship between the increase in near-bottom turbidity and intense wind episodes making plausible the incorporation of Chl a containing biomass in the water column during the wind episodes.…”
Section: Discussionmentioning
confidence: 96%
“…The larger impact of NW and E-NE wind episodes (in comparison of sea-breeze) on Chl a concentration was due to the characteristics of the bay, which is very shallow and microtidal. In this sense, winds > 10 m•s −1 (above typical sea-breezes intensities) immediately cause mixing in the water column and likely resuspension events [4,9,41]. Also, the duration of these strong winds associated with E-NE and NW events was a few days, compared to the strong winds that may occur during sea breeze periods, which are a few hours in length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wong et al [4] showed how the impact of the wind-induced coastal sea level at the entrance of an inlet exerts a huge impact on the subtidal variability within the interior of the bay. The influence of wind can also have effects on salinity structure or resuspension events in shallow estuaries [5][6][7][8]. These studies indicate that spatial scales and water depth determine the flow response to wind forcing.…”
Section: Introductionmentioning
confidence: 83%